Engagement in web-based learning system: An investigation of linear and nonlinear navigation - Katuk, Norliza; Zakaria, Nur Haryani (Springer International Publishing, 2015)
This paper investigates linear and nonlinear navigations in Web-based learning (WBL) systems. The aim of the study was to identify whether the linear and the nonlinear navigations could be the factors that influence students’ engagement within WBL environment.An experimental study was conducted on seventy-two students from a university in Malaysia using a Web-based system for learning Basic Computer Networks and a self-report inventory. The results of this study suggested that the types of navigation support affected engagement from certain aspects.